2018
DOI: 10.1111/1365-2664.13169
|View full text |Cite
|
Sign up to set email alerts
|

Coastal wetland adaptation to sea level rise: Quantifying potential for landward migration and coastal squeeze

Abstract: Coastal wetland ecosystems are expected to migrate landwards in response to rising seas. However, due to differences in topography and coastal urbanization, estuaries vary in their ability to accommodate migration. Low‐lying urban areas can constrain migration and lead to wetland loss (i.e. coastal squeeze), especially where existing wetlands cannot keep pace with rising seas via vertical adjustments. In many estuaries, there is a pressing need to identify landward migration corridors and better quantify the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
93
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 78 publications
1
93
0
1
Order By: Relevance
“…Our review suggests that widespread sea-level driven submergence of low-lying land will continue in the 309 future, even under scenarios of coastal population growth and large-scale defense of urban areas. 310 However, land conversion will largely take place on privately owned land 82,86 , where landowner 311 attitudes and adaptation efforts suggest local resistance 70 . We therefore pose the following 3 questions 312 to guide future research and land management decisions: 313 314 1.…”
Section: Recommendations For Future Research 308mentioning
confidence: 99%
See 4 more Smart Citations
“…Our review suggests that widespread sea-level driven submergence of low-lying land will continue in the 309 future, even under scenarios of coastal population growth and large-scale defense of urban areas. 310 However, land conversion will largely take place on privately owned land 82,86 , where landowner 311 attitudes and adaptation efforts suggest local resistance 70 . We therefore pose the following 3 questions 312 to guide future research and land management decisions: 313 314 1.…”
Section: Recommendations For Future Research 308mentioning
confidence: 99%
“…Research in the last 5 years has identified 315 and mapped large barriers to wetland migration such as urban land and publically owned levees at 316 regional scales 77,[80][81][82] . However, the majority of vulnerable land is located on private property in rural 317 areas 38,82,87 . Future research should investigate the efficacy of local and privately maintained barriers 318 such as berms, ditches, and secondary roads, and the probability and consequences of barrier failure.…”
Section: Recommendations For Future Research 308mentioning
confidence: 99%
See 3 more Smart Citations